Uso de escores de gravidade como preditores de morbidades no período neonatal - Wouters, Júlia Drebes (2021)
Due to the advances in neonatal care it has been possible to reduce the mortality in preterm infants and those with extremely low birth weight, although, their survivor has been followed by majority morbidities. The neonatal severity scores aim to classify the infant condindition in admission at the Neonatal Intensive Care Unit (NICU) and are an important tool for survivor prediction. However, the potential use of these tools as morbidities prediction has been suggested, but not widely used. The purpose of this study is to assess the ability of the neonatal severity scores SNAP II, SNAP-PE II, CRIB and CRIB-II as predictors for neonatal morbidities as Bronchopulmonary Dysplasia, Retinopathy of Prematurity and Peri/Intraventricular Hemorrhage and/or Periventricular Leukomalacia. This study is an observational prospective cohort and the population was composed of newborns admitted in HUSM NICU in the period of 1 year. Those who evolved to death within less than 12 hours of life and those within malformations or genetic syndromes incompatible with life were excluded. The data was extracted from the patient's medical record, the scores were applied and the morbidity presence avalueted. 201 infants were included, the median gestational age was 34 weeks, while the median birth weight was 1815 grams. Classic BPD was the most prevalent morbidity, being present in 13,5% patients. The presence for 2 or more morbidities was found in 9% of the total studied. SNAP-PE II had the best association to “classic” BDP (sensibility 81,48%, specificity 79,46% and area under the ROC curve 0,7492 0,73 (IC 0,623-0,840)) and also to “new” BPD (sensibility 69,23%, specificity 75,53% and area under the ROC curve 0,80 (IC 0,692- 0,914)). For those born with very low birth weight, CRIB score showed area under the ROC curve 0,7952 (IC 0,666-0,923). In due to ROP, the SNAP-PE II and CRIB II scores showed similar results: sensibility 68,75%, specificity 79,46% and area under the ROC curve 0,7492 (IC 0,611-0,811); sensibility 100%, specificity 54,14% and area under the ROC curve 0,7532 (IC 0,618-0,887), respectively. With regard to cerebral injuries SNAP-PE II was also superior within an area under the ROC curve 0,72 (IC 0,567-0,879), sensibility 75% and specificity 65,95%. The use of severity scores as morbidity predictors shows promising, within good to excellent sensibility, especially when it comes to SNAP-PE II. In very low birth weight preterms, CRIB II also stands out as a predictor for ROP and “new” BDP.